Multicultural Social Justice and Human Rights: Strategic Professional Development for Social Work and Counseling Practitioners - Jessica A. Barrett (Journal for Social Action in Counseling and Psychology)
Social work and counseling practitioners routinely provide services to clients of diverse cultural backgrounds. Multidimensional issues related to human diversity, social justice and human rights often prevent practitioners from providing competent and effective services to all populations. It is vital that these professionals focus on individual leadership development from a multicultural social justice perspective. The concept of social justice challenges existing structures and when paired with the human rights paradigm can significantly impact competent and ethical service delivery and practice. A focus on professional development among students, new professionals, and experienced practitioners can aid individuals in implementing human rights and social justice strategies within individual practice, organizations and communities.